Strategic Environmental Assessment in marine spatial planning of the North Sea and the Baltic Sea – An implementation tool for an ecosystem-based approach?. (August 2021) - Pinkau, Anne; Schiele, Kerstin S.
Abstract: With the enactment of the European Maritime Spatial Planning Directive many coastal Member States are confronted with the challenge of applying Strategic Environmental Assessments (SEAs) in the context of setting up marine spatial plans for the first time. In addition, they are obliged to apply an ecosystem-based approach (EBA) in their new marine/maritime spatial planning (MSP) frameworks. This study examines how the emerging practice of applying SEAs in MSP contributes to the implementation of an EBA. Five case studies from the North Sea and the Baltic Sea marine regions are investigated. The assessment framework is based on the EBA key elements that members of the Baltic Marine Environment Protection Commission and Visions and Strategies around the Baltic Sea agreed upon. The findings of this study underline that SEAs in MSP are potentially a valuable implementation tool for an EBA. However, so far planning reality lacks behind this potential. Analysis shows that not yet all criteria for EBA key elements are addressed in the case studies. In particular, 'alternative development', 'precaution' and 'adaptation' require more specific actions. Key elements were often addressed in a general manner, not reaching the stage of explicit measures. It is necessary to refine vague concepts, to operationalise principles and to advance in knowledge and comparable and transparent methodologies to meet the demands of an EBA. Recommendations are given how to close the gaps from an EBA perspective. Highlights: SEA is a valuable implementation tool for an EBA in MSP, if effectively applied. Emerging marine SEA practise stays behind its potential from an EBA perspective. There is a lack of detailed SEA guidance for marine space. SEA must be supported by other mechanisms to fully achieve ecosystem-based MSP.